Student-led development and evaluation of a community pharmacy-based cardiovascular risk assessment. (2015) - Filion-Murphy, Christine; Hands, Lyndsey; Hockham, Lyndsey; Kirkpatrick, Laura; McNamara, Sinead; Strath, Alison; Rowe, Iain; Vosper, Helen
No abstract available